The Land Question and Development - Fernandez, Artchil (Social Sciences and Development Review, 2023)
There are growing concerns that the social justice provision of the Philippine Constitution where agrarian reform is embedded will be abandoned by future governments intent on market solutions to poverty and late development. This paper disagrees and argues for the need to extend the land reform program in the light of the current issues faced by the country. It contends that agrarian reform is a crucial ingredient to address the late development status of the Philippines. The paper makes it case by first tackling the role of agriculture in development. It next discusses the pathways to economic development with land reform as a vital component. Lastly it argues for the extension of the land reform program as a key component for the development of the Philippines.